Study of Mortality Acanthopagrus Latus Fish in Iraq - Ali Balash Jebur1 , Rasha Abdulameer Jawad2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
This study was conducted in Iraq in Karbala during the winter period in December and January of each year.The study aimed to know the causes of fish death in large numbers. Acanthopagrus Latus By investigatingthe most important causative factors by taking random samples of infected fish in Lake Razazah, it wasnoticed through a study of the appearance of these fish that they have severe laceration with clear redness inthe abdominal area and specifically near the opening of the complex, which extends to the dorsal area nearthe gills cover Over time, in some of the studied samples, the tissue culture of the affected area indicatedthe presence of a fungus Aspergillus Niger Which may be one of the causes, our conclusion caused by thedeath of fish Acanthopagrus Latus In addition, someone has approximately (12) types of yeasts found inthese infected fish.